Global burden of gout among young people from 1990 to 2021, with projections for 2050: A systematic analysis based on the Global Burden of Disease Study 2021 - Peipei Tian; Hailiang Zhao; Botao Wang; Yanpeng Chen; Zhijun Jia; Chao Wang; Guangya Wang (PLoS ONE, 2025)
Gout represents the most common form of inflammatory arthritis, exerting a substantial impact on patient quality of life and productivity. In recent years, the age distribution of gout has shifted, with an increasing incidence among younger individuals. Accurate statistics regarding the incidence, prevalence, and disability-adjusted life years (DALYs) associated with gout in this population are critical for effective resource allocation in prevention and treatment strategies. In the current study, data from the 2021 Global Burden of Disease (GBD) database were used to analyze the burden of gout among young people aged 15–44 years in 204 countries and territories from 1990 to 2021, with projections extending over the next 25 years. Data on prevalence, incidence, and DALYs were collected and stratified by geographical location, gender, and economic development level. Decomposition analysis and predictive modeling were employed to evaluate trends and the impact of critical indicators. In 2021, 8,516,229 young individuals were affected by gout globally, with 1,975,165 new cases and DALYs totaling 283,725 person-years. Since 1990, the age-standardized prevalence rate, age-standardized incidence rate, and age-standardized DALYs rate increased by 10.4%, 9.4%, and 10.2%, respectively, all showing positive correlation with the sociodemographic index ( r = 0.319, 0.272, 0.320, P < 0.001). It is projected that by 2046, global figures in young people will reach approximately 9,229,870 total cases, 2,202,802 new cases, and 307,441 DALYs. Males are anticipated to account for 7,460,349 affected individuals, 1,762,412 new cases, and 245,542 DALYs, whereas females will represent 1,769,521 affected individuals, 440,390 new cases, and 61,899 DALYs. The global disease burden of gout among young people increased significantly from 1990 to 2021, and it is expected to continue rising over the next 25 years. Comprehensive epidemiological data remain essential for guiding gout prevention and management, as well as shaping effective health policies.